2001
DOI: 10.1007/bf02673871
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of splicing proteins and putative coiled bodies during pollen development and androgenesis in Brassica napus L.

Abstract: Small nuclear ribonucleoprotein particles (snRNPs) are subunits of splicing complexes, which show a transcription-dependent localization pattern. We have analyzed the labelling pattern of snRNPs during pollen development and microspore and pollen embryogenesis in Brassica napus with an antibody which recognizes protein D of U1, U2, U4, U5, and U6 snRNPs. It was found that nuclei were labelled almost uniformly for snRNPs in microspores and young bicellular pollen. In the generative nuclei of late-bicellular pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 42 publications
0
18
1
Order By: Relevance
“…We used the mouse mAb 7.13, which recognizes the SmD protein of the Ul, U2, U4, U5, and U6 snRNPs in plants (Billings et al 1982, 1985; Pálfi et al 1989; Testillano et al 1993; Straatman and Schel 2001). Immunoprecipitation and western blot analyses demonstrated that the mouse monoclonal anti-SmD antibody recognized a band with a molecular mass of about 55 kDa (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the mouse mAb 7.13, which recognizes the SmD protein of the Ul, U2, U4, U5, and U6 snRNPs in plants (Billings et al 1982, 1985; Pálfi et al 1989; Testillano et al 1993; Straatman and Schel 2001). Immunoprecipitation and western blot analyses demonstrated that the mouse monoclonal anti-SmD antibody recognized a band with a molecular mass of about 55 kDa (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been shown that the number of CBs in plant cells changes during the cell cycle and differentiation (Boudonck et al 1998; Straatman and Schel 2001; Seguí-Simarro et al 2006; Zienkiewicz and Bednarska 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Our knowledge about the state of the cellular splicing machinery organization in germ line cells of angiosperms still remains poor. Few and fragmentary data concerning the localization of splicing molecules came from studies on pollen cells (Concha et al 1995;Straatman and Schel 2001;Fang et al 2004;Zienkiewicz et al 2006) and pollen tubes (Zienkiewicz et al 2008). So far, there are no reports about the spatial organization of gene expression in flowering plant female gametophyte cells.…”
Section: Introductionmentioning
confidence: 99%
“…These splicing factors accumulate in Cajal bodies (Raska et al, 1990;Ferná ndez et al, 2002). Antibodies to splicing factors revealed these nuclear bodies as small bright spots (Moreno Díaz de la Espina et al, 1982;Testillano et al, 1993;Straatman and Schel, 2001).…”
Section: Presence Of Cajal Bodies Increases With Proliferative Activitymentioning
confidence: 99%
“…Nuclear bodies and specifically Cajal bodies are apart from the nucleolus and heterochromatin masses, one of the most evident nuclear substructures which have been found in numerous differentiated and proliferating animal cells (reviewed in Gall, 2000), as well as in some plant cells (Moreno Díaz de la Espina et al, 1982;Straatman and Schel, 2001). Cajal bodies (CBs) are rounded structures ranging from 0.1 to 2.0 Ìm, related to interchromatin granules, and showing an ultrastructure, in most cell types, of packed coiled threads (Raska et al, 1990;Lafarga et al, 1998).…”
Section: Presence Of Cajal Bodies Increases With Proliferative Activitymentioning
confidence: 99%